Silver Nanoparticles Synthesized through Green Methods Using Escherichia coli Top 10 (Ec-Ts) Growth Culture Medium Exhibit Antimicrobial Properties against Nongrowing Bacterial Strains - Baltazar Encarnación, Esther; Escárcega González, Carlos Enrique; Vasto Anzaldo, Ximena G.; Cantú Cárdenas, María Elena; Morones Ramírez, José Rubén (Hindawi Publishing Corporation, 2019)
Finding novel antibiotics and antimicrobial materials has become of great importance to modern society due to the alarming increase in the development of multidrug resistance in various bacterial strains. This problem is even more complex when infections involve bacterial strains in stationary metabolic states, since most of the antibiotics found in the market do not have an effect on bacteria in dormant metabolic states. A promising field to aid in the solution of this problem is nanotechnology, since it offers a wide avenue for the development of potential therapeutics, specifically the use of silver metal nanoparticles. Silver nanoparticles have proven to be highly effective antimicrobial agents and excellent candidates to be engineered and designed into clever delivery systems, taking advantage of their rapid and potent toxicity on prokaryotic cells at low concentrations. Metal nanoparticles are most commonly synthetized through one or a series of redox chemical reactions using powerful but environmentally toxic-reducing agents. Therefore, in this work, we propose a biosynthesis method that allows the production of nanoparticles, with homogenous shapes and narrow size distributions, through an environmentally friendly technique that does not produce toxic residues. Here, silver nanoparticles were produced from silver salt (AgNO3) using three different growth culture media residues from E. coli top 10. The three different culture media residues used included LB, LBN, and LBE; all of them displaying a different chemical and nutrient composition. Here, after characterization of the different silver nanoparticles produced with the different media, we demonstrated that the LB culture-conditioned media was the most suitable to produce them since they displayed the most narrow size distribution, with an average 10.6 nm in diameter, a relatively low standard deviation of 5.5 nm, and a narrow UV-vis spectrum absorption peak at 420 nm. The other methods presented larger nanoparticle sizes and broader size distributions. Furthermore, nanoparticles produced with LB Lennox were found to be, at very low concentrations, effective antimicrobial agent against E. coli top 10 at stationary phase. Therefore, these results seem to contribute knowledge linked to the production of antimicrobial nanoparticles (Ag-NPs) through green synthesis and represent a platform to treat infections caused by nongrowing bacteria.